Sjögren's syndrome with paresis of the internal branch of the superior laryngeal nerve. Issue 6 (November 2014) - Nihei, Yoshihiro; Ito, Daisuke; Uno, Kosuke; Saito, Koichiro; Kameyama, Kaori; Ando, Makiko; Ishikawa, Aiko; Takahashi, Shinichi; Nogawa, Shigeru; Koto, Atsuo; Suzuki, Norihiro
Abstract A 46‐year‐old woman developed painful dysesthesia in her extremities and ataxic gait. She was diagnosed with Sjögren's syndrome, and her condition was diagnosed as sensory ataxic and painful neuropathy. Intravenous immunoglobulin therapy alleviated the ataxia and severe pain in her extremities. When she was 61‐years‐old, she developed dysphagia and dyspnea. Laryngoscopy showed tactile anesthesia on the epiglottis, indicating paresis of the superior laryngeal nerve. We considered that the primary cause of dysphagia was paresis of the internal branch of the superior laryngeal nerve, and carried out tracheostomy and high‐dose intravenous methylprednisolone therapy (1 g/day × 3 days). Her dysphagia and aspiration gradually improved without following oral steroid therapy. Our case is the first report of the internal branch of superior laryngeal nerve paresis as a possible cause of dysphagia and aspiration in a patient with Sjögren's syndrome. Additional cases of Sjögren's syndrome with dysphagia should be investigated to confirm our findings.